Governance in Waste Management: An Analysis of the Implementation of Qanun No. 4 of 2017 in Aceh Barat - Debi Pahla Nolita; Ilham Mirza Saputra (Universitas Teuku Umar, 2026)
Waste management remains a persistent challenge in many regions of Indonesia, including Aceh Barat, where waste generation continues to rise annually. To address this issue, the local government enacted Qanun No. 4 of 2017 on Waste Management, which aims to establish a clean, healthy, and sustainable environment. This study examines the implementation of the regulation through the governance perspective using Van Meter and Van Horn’s policy implementation model. Employing a qualitative case study approach, data were collected through in-depth interviews with key stakeholders and direct field observations in areas where unmanaged waste persists. The findings reveal that although the qanun has been formally implemented, its execution is not yet optimal. The main obstacles include limited community participation in proper waste disposal and insufficient knowledge among waste management officers regarding the regulation. Strengthening community engagement, improving the capacity of implementing officers, and enhancing monitoring mechanisms are essential to ensure more effective governance of waste management in Aceh Barat.